2022
DOI: 10.3390/ijms23169344
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Bowel Disease: A Review of Pre-Clinical Murine Models of Human Disease

Abstract: Crohn’s disease (CD) and ulcerative colitis (UC) are both highly inflammatory diseases of the gastrointestinal tract, collectively known as inflammatory bowel disease (IBD). Although the cause of IBD is still unclear, several experimental IBD murine models have enabled researchers to make great inroads into understanding human IBD pathology. Here, we discuss the current pre-clinical experimental murine models for human IBD, including the chemical-induced trinitrobenzene sulfonic acid (TNBS) model, oxazolone an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(43 citation statements)
references
References 156 publications
0
28
0
Order By: Relevance
“…Colon inflammation was scored following a published scoring system for induced colitis 18 , with modifications (Suppl. Table S2 ) to take into account the spontaneous nature of colitis in the present model and the histological differences, particularly with regard to tissue swelling observed in classical experimental models 19 . As can be seen from Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Colon inflammation was scored following a published scoring system for induced colitis 18 , with modifications (Suppl. Table S2 ) to take into account the spontaneous nature of colitis in the present model and the histological differences, particularly with regard to tissue swelling observed in classical experimental models 19 . As can be seen from Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The common preclinical murine models of UC include the DSS-induced colitis model, trinitrobenzene sulfonic acid (TNBS)-induced colitis model and IL-10-deficient mouse model ( 20 ). Various studies have demonstrated that IL-10 suppresses inflammation in colitis by regulating innate and adaptive immune responses, such as promoting the expansion of Treg cells to suppress the immune response mediated by Th17 cells, which indicates that IL-10-deficient mice were not suitable for the present study ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite of few studies of MDSCs in IBD patients, a number of studies employed murine colitis models to explore the functional roles of MDSCs. Dextran sulfate sodium (DSS)-induced, 4,6-trinitrobenzene sulfonic acid (TNBS)-induced, T cell transfer-induced or genetic defects-induced spontaneous murine colitis models were established to mimic the pathology of IBD ( 50 ). Murine MDSCs were identified as CD11b + Gr-1 + cells in most studies.…”
Section: The Dual Role Of Mdscs In the Development Of Ibdmentioning
confidence: 99%